Smoking among muslim students behavior case study in Surakarta - Reqyrizendri, Dyotisaddha; Prihartanti, Nanik; Asyanti, Setia (Indigenous, 2020)
Abstract. Based on various studies, cigarettes are harmful to the health of both active and passive smokers. That is the reason The Fatwa and Islamic Research Council, The Central Board of Muhammadiyah forbidding smoking behavior (haram). Nevertheless, many muslim students at University smoke. Thepurpose of this study is to descibe smoking behavior of Muslim students in Surakarta. The informants are active smokers (n=119) determined by purposive sampling. This study uses qualitative research methods with an exploration approach. The result shows that the students initiate their smoking behavior sincejunior high school. The internal factors that affect smoking behavior are the need for pleasure, existence, acceptance of social environment and stress coping. The external factors consist of social and family environment that have smoking habit. Smoking behavior continues because students tend to consider short-term benefits (psychological and social) rather than the long term health risks. The active smokerstudents do not identify themselves as part of the Muhammadiyah community therefore they do not concern about the Fatwa issued by The Central Board of Muhammadiyah. Most students want to quit smoking for two reasons: the encouragement of the closest people who object to smoking behavior andfeeling a deterioration in health.Keywords: muslim; smoking behavior; university student